Development of Math Set Game to Improve Critical Thinking Skills Student of Class VII Material Set - Rizqi Nurjanah (AlphaMath : Journal of Mathematics Education, 2022)
This research is a type of Research and Development (R&D) research that tests the validity, practicality, and effectiveness of Math Set Game media. Math Set Game media is a medium developed in the learning of students of mathematical set materials and one of the digital learning media by utilizing RPG Maker MV media as the basic system in its development. The development model used in this research is the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The data obtained from this study is quantitative data obtained from the results of expert review materials, the results of media expert reviews, student response results, and the results of critical thinking skills tests of students as many as 30 people. The data collection technique used is a) validation; b) questionnaire; and c) the critical thinking capability test with the instrument used is a) validation sheet; b) response questionnaire sheet; and c) critical thinking ability test sheet.  Based on the research that has been carried out, data has been obtained that shows that math set game media is valid, practical and effective in improving the critical thinking skills of students set materials so that math set game is worth using in learning and can be disseminated for educational purposes.